O ensino de História e suas implicações no contexto escolar: uma análise ontológica - Ferreira, Dávillo de Lima (2024)
The social and scientific relevance of this research lies in the understanding that History is an area of the human sciences that sees man as an agent who modifies the social world in a dialectical relationship. In our view, history is movement, which is constituted through crises, revolutions, ruptures and contradictions. The overall aim of this dissertation is to understand Marxism's conception of history and the implications for school education in the early years of elementary school, verifying the appropriation of historical-scientific concepts for the formation of the subject, and finally to analyze, through Marxian ontology, the teaching of history in the early years of elementary school, proposing educational activities of an emancipatory nature. In order to achieve an investigation that unveils the real, the mode of research adopted in this text is the theoretical-bibliographical with empirical research with the presentation of pedagogical activities - emancipatory educational activities according to Tonet's studies - a kind of memorial in the teaching of History in the early years, from the perspective of the Marxian legacy. For didactic purposes, we rely on authors who seek to rescue the revolutionary character of Marxism and highlight the Marxian legacy as an ontology of social being, such as: Lessa (2008), Tonet (2005) (2008), Netto (2011), and above all the classic authors who underpin our research such as Marx (2004) (2015) and Lukács (1978) (1979) and others. To this end, Labor, the founding category of social being, is understood as the basic premise of this study. It also considers the value of historical-scientific knowledge, but also points out that the teaching of history follows the logic of the degeneration of the human race, as well as the fragmentation of knowledge accumulated over the course of history, which is sidelined in Brazilian schools. By way of conclusion, he points out that there are possibilities and limits in teaching, but that it is possible to apply emancipatory educational activities with the aim of articulating the working class in the struggle to overcome capitalism, because the need to have human emancipation as a major project as a horizon, in today's context of postulated sociability, is urgent.